SMART GOVERNMENT DALAM RANGKA MEWUJUDKAN SMART CITY DI KOTA BANDUNG - Eko Budi Santoso; Annisa Rahmadanita (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2020)
This article describes the results of research conducted to determine the implementation of smart governance in supporting the realization of a smart city in Bandung, especially in implementing smart government. The research method is carried out with a descriptive qualitative approach based on the concept of smart governance according to Cohen (2014), which includes 3 dimensions, namely online services, infrastructure, and open government. The results showed that Smart government in order to realize a smart city in Bandung City, seen from these 3 dimensions, generally shows the characteristics that support the realization of a smart city in Bandung City. Of the three aspects, there is 1 (one) dimension whose characteristics are less supportive, namely the infrastructure aspect. In this infrastructure dimension, there are problems in terms of optical fiber shortages, server ownership and data center. There is also no infrastructure mapping according to the needs of the Bandung City Government in implementing smart government. Therefore it is suggested that the City Government of Bandung can prepare a map of the need for planning and infrastructure development in implementing smart government in order to realize a smart city in Bandung City. Kata Kunci: Smart Government, Smart City, Kota Bandung